Economic Problem of Women Headed Families after the Civil War: Special Reference with Maritimepettu (Karaithuraipatru) GN Division - Rewathy, K. (Ruhunu University International Conference on Humanities and social sciences, 2017)
This paper estimates whether female-headed households are poorer with the income they are earning and how they could overcome with the low level economy. Questionnaire survey method used for the data gathering as well as observation. Measuring of economy level and livelihood develop of women headed households reflected the meaningful outcome. The objectives are, to identify the economic problems of WHF and to find out their way of solving the problems. Most of the Widow women complaining that they loss their husband in the civil war period at Mullivaikal. Since that they are suffering without healthy economy and better livelihood. The result from the analysis provide evidence that the relationship between female headed households and economy problem depends on the work that they lean on, relations that they are depended, and the children that a family has. Specially, poor economy based on the housing condition and the wealth indices show that female headed households are less poor with their income level. But they are having some psychological and mental sickness. So, they need some special assistance for their family support care. Key Words: Economy, Income, Poverty, Women Headed Family, War